2021
DOI: 10.1186/s12891-021-04511-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of depressive symptoms and risk of knee pain: the moderating effect of sex

Abstract: Background Depression has been shown in some studies to be associated with knee pain. Females were widely recognized as more vulnerable to depression and knee pain than males. However, the role of sex in this correlation was under-researched. This study aimed to investigate the association between depressive symptoms and subsequent knee pain, as well as whether and how sex would moderate this association based on a four-wave (Wave 1 in 2010–2011, Wave 2 in 2013, Wave 3 in 2015, and Wave 4 in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Previous studies ( 28 ) have concluded that people with pain are more likely to fill in hearing impairment,; the two may be in an interactive relationship that needs to be further studied. Additionally, this study found that middle-aged and older adults suffering from depression were more likely to experience pain, which further supports the idea that the management and prevention of depression have great potential to improve physical pain in middle-aged and older adults ( 29 ).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies ( 28 ) have concluded that people with pain are more likely to fill in hearing impairment,; the two may be in an interactive relationship that needs to be further studied. Additionally, this study found that middle-aged and older adults suffering from depression were more likely to experience pain, which further supports the idea that the management and prevention of depression have great potential to improve physical pain in middle-aged and older adults ( 29 ).…”
Section: Discussionsupporting
confidence: 82%
“…The relationship between sex, mental health, and its correlation with MSK pain showed con icting evidence in the literature. Some studies have suggested that women are more likely to report depression and higher pain severity of chronic pain than men [14]; however, Hu et al (2021) found that males had a stronger correlation between knee pain and depression as compared to females [21]. Considering the low response rate from male students, further studies with more representation are warranted to understand the role of mental health in MSKDs and how this relationship differ between sexes.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between sex, mental health, and its correlation with MSK pain has shown conflicting evidence in the literature. Some studies have suggested that women are more likely to report depression and higher pain severity of chronic pain than men [ 15 ]; however, Hu et al (2021) found that males had a stronger correlation between knee pain and depression as compared to females [ 24 ]. Considering the low response rate from male students, further studies with more representation are warranted to understand the role of mental health in MSKDs and how this relationship differ between sexes.…”
Section: Discussionmentioning
confidence: 99%